Agricultural lands market in foreighm countries and in Ukraine: the problems of prices and of institutional environment - Tretiak А.; Tretiak, N. (Land Management, Cadastre and Land Monitoring, 2018)
To this day, the ongoing land reform has not yet ensured the formation of an effective market of land shares (shares) in our state. To this day, the ongoing land reform has not yet ensured the formation of an effective market of land shares (shares) in our state. Investigating the land market as a complex of economic and land management legal mechanisms those provide the establishment, change and termination of rights to land plots, which takes place on the basis of a legally enforceable agreement and is mediated by a cash payment, it is imperative to investigate the demand for land plots consisting of agricultural and non-agricultural demand. This is important because agricultural demand for land plots (land use) is a derivative of the demand for food created in crop and livestock production, and takes into account the level of soil fertility and the potential for its increase through land improvements, as well as their location, i.e, the remoteness from the centers of food consumption and raw materials. Demand for food is inelastic, as the volume of demand for basic foodstuffs varies insignificantly even with a significant change in prices. Non-agricultural demand has a steady upward trend in a stable economy of the country. This is a demand for land plots for the construction of housing, infrastructure, roads and other objects. Non-agricultural demand, as a rule, is indifferent to the level of soil fertility, but to a large extent depends on the location of the land. Considering that agricultural lands make up to 70.8% of the territory of Ukraine, so it is understood the importance of studying the agricultural land market in the country with the use of foreign experience.In this regard, the article examined the foreign experience of countries with a civilized market economy, in particular agricultural lands, which occupy a significant part of the country in Ukraine. For this purpose, the main factors influencing the value of agricultural land, namely, comparative productivity and value of agricultural land, are considered. A comparative estimation of the value of arable land inUkrainewas made on the basis of the normative monetary valuation and market value. In addition, to study the trends of changes in the value of agricultural land inUkraine, we will use the analysis of prices for the lands under buildings. It was discovered that the lack of a full system of guaranteeing land ownership rights and the lack of appropriate subsidies for the development of agricultural land use and rural infrastructure contributes to a reduction in the market value of land. It is also confirmed that sales prices in well-developed markets are roughly equal to the magnitude of capitalization of the economic return on land lease. It was established that the fundamental reason for the underdevelopment of the market of land parcels of land parcels owners is the imperfect institutional environment, in particular, the system of land rights guarantee, the system of land management and land management (the study will be carried out in the following article), the cadastre and land tenure system, the lease system relations, poor infrastructure of value added in agriculture as a whole. Key words: land market, market price, normative monetary estimation, land capitalization, agricultural land.